Design, Testing Analysis of High Tension Increased Safety Motor for Hazardous areas - Bhagirath Ahirwal; Tarun Kumar Chatterjee (Institute of Advanced Engineering and Science, 2015)
The increased safety (Ex e) motors are designed for safe operation in the zone 1 and 2 hazardous areas. The present paper describes the significant design parameters and successful testing of Ex e high tension (HT) induction motor rated 970KW/6.6KV/18 pole/ 3Phase/ 50Hz as per IS/IEC 60079-7 standard. The comparison of some useful design parameters is also given between safe area motor and hazardous area motor in this paper. The Ex e high tension induction motor mentioned in this paper have been manufactured by Bharat Heavy Electricals Ltd. (BHEL), Bhopal, India during the project and main author was the project leader.